Micro, small, and medium-sized enterprises, digital platforms, and competition policies in Asia - Atsuko Izumi; Yasuyuki Sawada; Yasutora Watanabe; Yesim Elhan-Kayalar (Asian Development Bank (ADB), 2023)
In this paper, we review the overall micro, small, and medium-sized enterprise landscape in Asia, including the challenges and constraints faced by enterprises in physical (offline) and online markets. We then explore the unique circumstances and externalities that arise due to the special characteristics of platforms and how they impact merchants and other platform users. Our findings suggest that the unique features of platforms, and the two-sided market structure they foster, require a bespoke policy approach from competition authorities and policymakers.
Keywords: K21; L41; L44; 330; competition policy; two-sided market; platforms; MSMEs